Autonomous Robot Path Planning Using Ant Colony Optimization and Evolutionary Programming - Via, Yisti Vita; -, Sugiarto; Nudin, Salamun Rohman (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This paper proposed an evolutionary approach for mobile robot path planning. The proposed method combines the Ant Colony Optimization algorithm as a local search procedure and the Evolutionary Programming algorithm to optimize the feasible path found by a set of local procedures. It explores the Ant Colony Optimization algorithm to determine the shortest feasible path from any current position to the target position in unknown environment with static obstacles. Criteria used to measure planning effectiveness include the path length and the smoothness of planned paths.Keywords : Mobile robot, path planning, Ant Colony Optimization, and Evolutionary Programming.Â